1997
DOI: 10.1002/(sici)1097-0215(19970220)74:1<31::aid-ijc6>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of an association betweenChlamydia pneumoniae infection and lung cancer

Abstract: Epidemiological evidence suggests that airway obstruction is an independent risk factor for lung cancer and that this cannot be explained by active or passive smoking alone. Chlamydia pneumoniae infection has been associated with chronic bronchitis and its exacerbates. Our aim was to evaluate the association between chronic C. pneumoniae infection and risk of lung cancer among male smokers. Smoking males with lung cancer (n 5 230) and their age-and locality-matched controls were selected among participants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
103
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 19 publications
5
103
0
2
Order By: Relevance
“…5,10 In our study, C. pneumoniae-specific immune complexes and both IgG and IgA antibodies were associated with female lung cancer. A previous study of male Finnish smokers 5 indicated that chronic C. pneumoniae infection was associated with subsequent diagnosis of squamous cell and small cell carcinomas but not with adenocarcinoma.…”
Section: Dear Sirsupporting
confidence: 51%
See 2 more Smart Citations
“…5,10 In our study, C. pneumoniae-specific immune complexes and both IgG and IgA antibodies were associated with female lung cancer. A previous study of male Finnish smokers 5 indicated that chronic C. pneumoniae infection was associated with subsequent diagnosis of squamous cell and small cell carcinomas but not with adenocarcinoma.…”
Section: Dear Sirsupporting
confidence: 51%
“…1 Although the relation between respiratory Chlamydia psittaci infection (avian exposure) and female lung cancer remains open, [2][3][4] C. pneumoniae infection has been repeatedly shown to be associated with lung cancer in male smokers as defined by serum cotinine. [5][6][7] We have now evaluated the association between past infection with C. pneumoniae and female lung cancer in a case-control study nested in a cohort of 650,000 fertile Finnish women established in 1983.…”
Section: Dear Sirmentioning
confidence: 99%
See 1 more Smart Citation
“…13,[23][24][25] In this study we also found that histologic type, not HPV DNA type, is a more important parameter in the determining association between C. trachomatis and cervical cancer. Similarly, in two recent prospective studies of the association between C. pneumoniae antibodies and lung cancer, elevated risks were found for squamous cell cancers but not adenocarcinomas of the lung, 26,27 though another study did not find this difference by histologic type. 28 It may be that the underlying pathogenic mechanisms of Chlamydia in cancer are specific to squamous cell cancers.…”
Section: Discussionmentioning
confidence: 92%
“…These studies were performed in Caucasian populations and primarily among male smokers. 1,3,4 To our knowledge, only 1 study has demonstrated an association between chronic infection and lung cancer among women. 2 This study, nested within the Finnish Maternity Cohort, observed a smoking-adjusted 2-fold increase in risk of early-onset lung cancer among women with elevated IgA (Ͼϭ64) or IgG (Ն128) titers.…”
Section: Dear Sirmentioning
confidence: 99%